Watering of Eye its Cause and Management - Attaullah Shah Buithari, Fahad F Shaikh, All Muhammad Abbasi,Khan Muhammad Nangrejo (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the causes of watering of eye. Methods: This cross-sectional study was carried out at Ophthalmology OPD of KWIC Teaching Hospital Khairpur from January 2016 To June 2016. A total of 315 patients with complain of watering eye were enrolled in the study. Ophthalmic examination with slit lamp and general medical examination was performed, treatment was given and results were calculated. Results: Out of 315 cases, 211 (66.98%) were female and 104 (33.05%) were male who came to e, OPD for watering eye with age ranging from infant 1-,vo weeks to 80 years: most common causes found blockage in lacrimal drainage system 46.98", dr, eye 21.26%, punctul stenosis7,61%, ectropion 6.98%, entropion 6.03%, multiple causes 5.39(.0 and chronic dacryocystitis 5.71%. Conclusion: Watery eye is common condition different etiologies with most frequent blockage in lacrimal drainage system, which needs proper management to reduce the disease burden.